Kulturgeographische Beobachtungen in Nordwestschottland, besonders auf der Insel Skye: Auf Grund einer Reise im August und September 1952 - Wagner, Erika (ERDKUNDE, 1953)
The North-West of Scotland has always been a region of interesting problems both geographical and social. Difficult physical conditions such as lack of sunshine, coal summers, frequent and strong gales, and the poor soil limit the possibilities of human existence. The events of social history have emphasized these difficulties, especially the break-up of the clans after 1745 and the succeeding Clearances, and subsequently Highland population has been constantly depleted by emigration. The remaining population has, however, preserved the traditional ways of life, such as the use of the Gaelic language, the practice of constructing the black house the organization of the Township, and in some parts of the Outer Hebrides methods of agriculture similar to those obtaining a thousand years ago. To improve living conditions in these remote districts and to reduce the continuing emigration the government has given legal and financial aid to the crofters. Afforestation plans, hydro-electric schemes, revival of old cottagecrafts, together with the tourist industry are intended to increase possibilities of employment. But the most important seems to be the application of modern and scientific methods to crofting agriculture. All this may help to overcome the difficulties of an inimical environment.